The Effect of Salinity on Solamargine and Solasonine Contents of Solanum incanum Plants Grown in Oman - Sana S. Al Sinani; Elsadig A. Eltayeb (Sultan Qaboos University Journal for Science, 2015)
In addition to its traditional medicinal importance, Solanum incanum (thorn apple) is also a rich source of important cytotoxic glycoalkaloids such as solamargine and solasonine. The effect of salinity stress on solamargine and solasonine production by Solanum incanum plants grown in soil has been investigated. Salinity stress has been applied by adding NaCl to the soil, in concentrations: 0.0 (control), 75, 150, and 225 mM for 8 weeks. HPTLC method was used for analysis of solamargine and solasonine in leaves, stem and roots. A positive correlation was observed between 150 mM NaCl salinity and production of solamargine and solasonine in leaves. In roots, solamargine content was not affected by NaCl treatment, whereas solasonine content increased with a short-term salinity treatment. However, salinity seems to reduce the production of solamargine and solasonine in the roots of Solanum incanum. The possibility of using NaCl as an efficient and economical elicitor of glycoalkaloid production in Solanum incanum plants is rejected on the basis of the results obtained.